The Effect of Leadership and Organizational Culture on Organizational Commitment (Studied in PT. PLN Control and Power Plant Unit Minahasa) - Steven Set Xaverius Tumbelaka; Herningsih Sutri Lembong; Jessylistina Langie (AIBPM Publisher, 2019)
The objective of this study is to analyze and explain the effect of variables leadership and organizational culture on organizational commitment. This type of research is quantitative associative aims to answer the hypothesis. The sample used in this study, are 46 permanent employees at PT. PLN (Persero) Control And Power Plant Unit Minahasa and used multiple regression data analysis. These study results indicate that the significance values of the two variables are, 0.001 for Leadership variable and 0.006 for organizational culture variable. These results provide the conclusion that the leadership variable has significant effect on organizational commitment variable, because the significance coefficient 0.000